Electrophysiological study with oxonol VI of passive NO3- transport by isolated plant root plasma membrane. - Pouliquin, P (1999)
In contrast to animal cells, plant cells contain approximately 5-50 mM nitrate in cytosol and vacuole. The lack of specific spectroscopic probes, or suitable isotopes, impedes in vitro studies of NO3- transport. Reconstitution of root cell plasma membrane (PM) proteins in mixed soybean lipid:egg phosphatidylcholine allowed for the generation of large K+-valinomycin diffusion potentials (Em), monitored with the oxonol VI dye. Nevertheless, Em was restricted to approximately 130 mV by capacitor properties of biological membranes. This caused an increasing discrepancy at higher K+-Nernst potentials used for calibration. Therefore, Em was determined directly from the fluorescence of the dye free in buffer, bound at zero Em, and bound upon Em generation. Then, an electrophysiological analysis of the NO3--dependent dissipation rate of Em gave the net passive flux (JN) and the permeability coefficient to NO3- (PN). The plant root cell PM exhibited a strikingly large PN (higher than 10(-9) m s-1) at high Em (90-100 mV) and pH 6.5. At low Em (50-60 mV) and pH 7.4, PN decreased by 70-fold and became similar to that of the lipid bilayer. This agreed with the previous observation that 15 mM NO3- short-circuits the plant root PM H+-ATPase at its optimal pH of 6.5.